Examining the relationship between occupational health and safety practices and productivity levels in private health facilities in the central region of Ghana - Michael Afari Baidoo; Emmanuel Kumah; Saansong Omar Ansir Ahmed; Judith Ayormisi Fafali (BMC Public Health)
Abstract Introduction Literature has established that offering protection for workers’ health and safety is one method of preserving an organization’s human resources and increase worker productivity. The purpose of this study was to examine occupational health and safety practices among selected private hospitals in the central region of Ghana and how it affects work productivity. Methods This study was a descriptive cross-sectional quantitative study and structured questionnaires were used to collect data from 344 healthcare workers at sixteen (16) selected private health facilities in the Central Region of Ghana, through the convenience sampling technique. Data entry and analysis were conducted using Statistical Package for Social Sciences (SPSS). Results A greater majority of the respondents exhibited positive perceptions and attitudes towards occupational health and safety protocols. The healthcare facilities of almost 6 out of every 10 sampled respondents had high compliance levels with occupational health and safety measures. Also, Pearson correlation analysis revealed a significant positive relationship between OHS implementation and overall productivity (r(344) = 0.255, p < 0.018). This relationship remained significant after controlling for demographic variables through partial correlation analysis (r(344) = 0.272, p = 0.015), indicating a stable and consistent association. The most mentioned potential areas for improvement to optimize employee well-being and productivity were safety training, safety satisfaction and feedback and management safety commitment while the least mentioned were safety reporting, safety involvement and working environment. Conclusion This study has demonstrated that the implementation of OHS measures has a positive and significant relationship with the overall productivity of healthcare workers in private health facilities in the Central Region of Ghana.